Flourishing as a highly sensitive person: a mixed method study on the role of nature connectedness and chaotic home environment - Carroll, Susan; O’Brien, Anna; Lionetti, Francesca; O’Reilly, Anna; Setti, Annalisa (Frontiers in Psychology, 2025)
IntroductionTheories of Environmental Sensitivity postulate that those who are highly sensitive thrive in favourable contexts and are more disadvantaged by unfavourable ones; however, negative outcomes, instead of positive, are more often investigated. In this study, instead, we focus on human flourishing and what promotes it or hinders it. Recent literature shows that those who are highly sensitive are more connected with nature, and nature connectedness is known to confer psychological benefits. On the contrary, a chaotic home environment is associated with decreased well-being. We hypothesise that a chaotic home environment will negatively impact flourishing, particularly for those who are highly sensitive, while being connected with nature will have a more positive effect on them. Middle and older adulthood are less investigated stages of life.Methods856 participants aged 40+ were surveyed on their level of sensory processing sensitivity (SPS), flourishing, current chaos in the home, and nature connectedness. A subsample of 12 highly sensitive people were then interviewed to better understand the role of these dimensions in flourishing as a highly sensitive person.ResultsThe results from the quantitative analysis revealed that flourishing was positively associated with nature connectedness and age and negatively with higher SPS. Nature connectedness significantly moderated the relationship between sensitivity /and flourishing, while the level of chaos did not. This interaction was not significant in the youngest (40–49 years) cohort. Qualitative data from interviews with 12 participants provided deeper insights into the challenges faced by highly sensitive individuals, including emotional reactivity and feelings of being different, exacerbated by stressors such as noise and conflict at home. Participants reported significant benefits from nature.DiscussionOverall, the results showed that connecting with nature significantly contributes to flourishing in highly sensitive individuals, particularly in middle to older age. The findings support the potential of future nature-based interventions to promote flourishing in highly sensitive people.